(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2025)
The objective of this work is none other than to highlight the concern regarding the interpretation given to the freedom of education enshrined in Article 27 of the Spanish Constitution and in international treaties (to whom the constitution was rightly referred, precisely, to uphold the respect for this freedom). Many of the conflicts generated in reality stem from a series of limitations on this freedom that have accumulated due to a biased interpretation of it, which is improper for democratic and progressive regimes. Among such limitations, one that significantly affects university students is the deprivation (or extraordinary hindrance) of their mobility after being part of a specific university institution (for which all the requirements were met for access them), due to the way university autonomy has been exercised, which has not taken into account the freedom and the needs of the student.